Investigation of Microwave Irradiation Procedure for Synthesizing CdSe Quantum Dots - Jacob Strimaitis; Taliya Gunawansa; Sangram Pradhan; Messaoud Bahoura (Advances in Materials Science and Engineering)
In recent years, microwave heating techniques for quantum dot (QD) synthesis have come to supplement the typical hot-injection methods. In addition to increasing control and replicability, microwave synthesis can be up-scaled to industry standards, an advantage that increases its lucrativeness. This study depicts a strategy to take a hot-injection procedure for cadmium selenide (CdSe) QD synthesis that is safe enough for undergraduate research labs and adapt it to an easier, more energy-efficient microwave synthesis method. Additionally, this study details successes in synthesizing these QDs, along with some challenges, limitations, and peculiarities. For future users of this method, it is recommended to keep holding temperatures between 170°C and 240°C to achieve the highest monodispersity of CdSe QDs while also avoiding confounding effects, such as wide-spectrum photoluminescence and bulk CdSe precipitation.